2017
DOI: 10.1016/j.renene.2016.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the technical, environmental and economic potential of phase change materials (PCM) for root zone heating in Mediterranean greenhouses

Abstract: Root zone heating systems offer increasing crops quality and productivity. However, these systems are based on the use of nonrenewable fuels. This paper reports on a study of different design solutions for a root zone heating system, based on thermal energy storage with PCM. The objective of the study was to define, through multiple experiments, the most efficient PCM melting/freezing temperature and location with respect to the substrate (i.e., under the substrate) for the application under study; as well as,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…PCM Soil-less crops (10) are a design solution for a root zone heating system in Mediterranean greenhouses (Llorach-Massana et al 2017), as seen in Figure 12. They are based on thermal energy storage with phase change materials (PCM).…”
Section: Case Study 5 -Phase Change Materialsmentioning
confidence: 99%
“…PCM Soil-less crops (10) are a design solution for a root zone heating system in Mediterranean greenhouses (Llorach-Massana et al 2017), as seen in Figure 12. They are based on thermal energy storage with phase change materials (PCM).…”
Section: Case Study 5 -Phase Change Materialsmentioning
confidence: 99%
“…The use of recycled PCM and LDPE for encapsulation or an increase in the efficiency of the PCM production process could lead to a reduction in the operation days/year required to achieve environmental payback. Finally, concerning the economical assessment, the LCCA revealed that the application of PCM did not seem to be economically viable until installation and PCM prices fall significantly …”
Section: Life Cycle Analysis and Life Cycle Cost Analysis Of Pcms Formentioning
confidence: 99%
“…From 1949 till now, many experimental and theoretical studies took place concerning the use of PCM in solar heating of buildings. The application of PCMs in greenhouses, mainly for storing solar energy, is another wide field of ongoing research . Also, Abokersh et al reviewed the implementing work in utilizing PCM in various types of Solar Domestic Water Heating Systems.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review has revealed that an LCA of bio-based products has previously been conducted with respect to medium-density fiberboard (MDF) [37,38], oriented strand board (OSB) [39], particleboard [40], and laminated veneer lumber [41]. The environmental performance of PCM has been analyzed in several products including solar thermal systems [32,33], root zone heating systems [42], air conditioning systems [34], and solar thermal storage systems [35]. PCMs incorporated in building envelopes are widely studied in order to increase their thermal energy storage capacity [31,[43][44][45].…”
Section: Introductionmentioning
confidence: 99%